Primary Descemet's Membrane Endothelial Keratoplasty for Fuchs Endothelial Dystrophy versus Bullous Keratopathy: Histopathology and Clinical Results. (3rd October 2018) - Brockmann, Tobias; Brockmann, Claudia; Maier, Anna-Karina B.; Schroeter, Jan; Bertelmann, Eckart; Torun, Necip
ABSTRACT: Purpose : To investigate functional and anatomical results up to 12 months after Descemet's membrane endothelial keratoplasty (DMEK) for Fuchs' endothelial dystrophy (FED) versus bullous keratopathy (BK) in consideration of morphologic characteristics on host's endothelium-Descemet's membranes (EDM). Methods : In a prospective consecutive case series, 119 eyes underwent a primary DMEK for FED or BK. Intraoperatively obtained EDM were investigated immunohistologically. Clinical and morphological parameters were compared between FED and BK. Results : Overall, the 12-months best-corrected visual acuity (BCVA) was 0.14 logMAR, and 0.10 logMAR in eyes without vision-limiting comorbidities; thereby no differences were revealed between eyes with FED and BK up to 12 months postoperative ( p = 0.186 and p = 0.095, respectively). Correspondingly, the mean central corneal thickness (CCT) measured 520 vs. 529 µm and the mean endothelial cell density (ECD) was 1743 vs. 1457 cells/mm 2 for FED and BK, 12 months postoperative. Regarding CCT and ECD, no differences were observed between the groups ( p = 0.181 and p = 0.112, respectively). The overall detachment rate was 40% (48/119). Comparing FED and BK the detachment rates did not differ, which were 41% vs. 39% and 43% vs. 35%, in pseudophakic eyes ( p = 0.554 and p = 0.601, respectively). Yet, the distribution of recurring graft detachments differed between FED and BK; secondary re-detachments were more frequent in the FED group (7 cases). Regarding histologic investigations, a lower ECD was found in specimens with BK, no differences were revealed for EDM and anterior banded layer thicknesses. Immunohistologically, differences in the distribution of fibronectin and cytokeratin were observed. A rarification of matrix proteins was found in EDM complexes with FED. Conclusions : DMEK produces similar results for FED and BK. However, the postoperative course may differ with regard to the recurrence of secondary graft detachments that may be associated by histopathologic particularities.